TRANSFORMATION OF SOCIAL MOVEMENTS IN THE DIGITAL ERA: ANALYSIS OF THE ROLE OF SOCIAL MEDIA IN COLLECTIVE MOBILIZATION - Syahrir Ibnu (Social Studies and Humanities Journal (SOSHUM), 2025)
This study analyzes how social media transforms the structure, strategies, and dynamics of social movements in the digital era. Using a multidisciplinary approach,narrative reviewThis study synthesizes various academic literature and official agency reports from 2010–2025 to understand the evolution of social movements in the context of digital communication. The study's findings indicate that social media has transformed the structure of social movements from a hierarchical model to a flexible horizontal network, enabling collaboration without a single leader. Mobilization strategies have also shifted toward hashtag activism and digital storytelling which utilizes algorithms and public emotions to strengthen solidarity. The dynamics of participation are shifting from ideological solidarity to affective solidarity based on digital emotions. This study proposes a conceptual frameworkDigital Mobilization Framework (DMF)which integrates theoryResource Mobilization, Connective Action, And Affective Publicsto explain the new logic of social mobilization in the digital era.